![{x}^{3} + ( \frac{1}{x})^{3} = 110 {x}^{3} + ( \frac{1}{x})^{3} = 110](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B3%7D++%2B+%28+%5Cfrac%7B1%7D%7Bx%7D%29%5E%7B3%7D++%3D+110)
then find
![x + \frac{1}{x} = x + \frac{1}{x} =](https://tex.z-dn.net/?f=x+%2B++%5Cfrac%7B1%7D%7Bx%7D++%3D+)
Answers
Answered by
0
Solution:-
It's given that,
![{x}^{3} + { (\frac{1}{x} )}^{3} = 110 {x}^{3} + { (\frac{1}{x} )}^{3} = 110](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B3%7D++%2B++%7B+%28%5Cfrac%7B1%7D%7Bx%7D+%29%7D%5E%7B3%7D++%3D+110)
![(x + { \frac{1}{x} })^{3} - 3(x + \frac{1}{x} ) = 110 (x + { \frac{1}{x} })^{3} - 3(x + \frac{1}{x} ) = 110](https://tex.z-dn.net/?f=%28x+%2B++%7B+%5Cfrac%7B1%7D%7Bx%7D+%7D%29%5E%7B3%7D++-+3%28x+%2B++%5Cfrac%7B1%7D%7Bx%7D+%29+%3D+110)
![let \: (x + \frac{1}{x}) \: be \: m let \: (x + \frac{1}{x}) \: be \: m](https://tex.z-dn.net/?f=let+%5C%3A+%28x+%2B++%5Cfrac%7B1%7D%7Bx%7D%29+%5C%3A++be+%5C%3A+m)
So,
![{m}^{3} - 3m - 110 = 0 \\ m( {m}^{2} - 3) = 110 {m}^{3} - 3m - 110 = 0 \\ m( {m}^{2} - 3) = 110](https://tex.z-dn.net/?f=+%7Bm%7D%5E%7B3%7D++-+3m+-+110+%3D+0+%5C%5C+m%28+%7Bm%7D%5E%7B2%7D++-+3%29+%3D+110)
Now,
![m ({m}^{2} - 3) = 5( {5}^{2} - 3) m ({m}^{2} - 3) = 5( {5}^{2} - 3)](https://tex.z-dn.net/?f=m+%28%7Bm%7D%5E%7B2%7D++-+3%29+%3D+5%28+%7B5%7D%5E%7B2%7D++-+3%29)
Hence,
K=5
It's given that,
So,
Now,
Hence,
K=5
ggada:
Hello I have reported this question
Similar questions